Does the Office of Patient Experience Matter in Improving Delivery of Care?. Issue 4 (14th December 2019) - Sharma, Luv; Chandrasekaran, Aravind; Bendoly, Elliot
Abstract : This research examines the performance benefits of the Office of Patient Experience (OPX), a new administrative innovation in the health care industry. OPX is an independent structure within a hospital, having its own annual budget and full‐time staff, and is responsible for improving patient experience during the hospital stay. We specifically investigate the effectiveness of OPXs in improving experiential quality (EQ), measured as the quality of interactions between hospital's caregivers and patients. In addition, we look at how the operation of these offices help hospitals manage variability during the delivery of care, which introduces additional challenges to maintaining high EQ. Specifically, we investigate the impact of variability in care delivery introduced due to two factors—patient case mix index (CMI) and resident intensity. CMI is an indicator of patient acuity and their care burden on hospitals while resident intensity is measured as a ratio of residents to beds at a hospital and is a proxy for variability introduced due to disruptions in caregiver teams due to the presence of residents who are getting trained at the hospital. Our empirical analyses involve tracking the operation of these offices across 3615 US acute care hospitals for the years 2007–2014. To account for endogeneity, we used an instrumental variable fixed effects regression model with a least absolute shrinkage and selection operator (LASSO) on the first‐stage to identify and select the strongest instruments. Findings suggest that the OPX is associated with 1.95% higher EQ for each year of its operation. Furthermore, we find that an OPX is more effective in improving EQ for hospitals that deal with high CMI patients (6.5% for high vs. −0.3% for low) or high resident intensity (1.8% for high vs. 0.9% low). Moreover, we find evidence of operating efficiencies associated with OPXs, with a 1.4% reduction in operating cost for each year of its operation. Preliminary evidence also suggests that Chief Patient Experience Officers (CXOs), leaders of OPX, with medical backgrounds (i.e., MD or nursing degree) are more effective at improving EQ. Finally, we validate our findings through interviews with OPX and hospital staff at a prominent teaching hospital with an active OPX.